Steroid Receptor Coactivator-3 Promotes Bladder Cancer Through Upregulation of CXCR4 - Zhang, Yu; Wang, Ji-Hong; Liu, Bin; Qu, Ping-Bao (Asian Pacific journal of cancer prevention : APJCP, 2013)
The three homologous members of the p160 SRC family (SRC-1, SRC-2 and SRC-3) mediate the transcriptional functions of nuclear receptors and other transcription factors, and are the most studied of all the transcriptional co-activators. Recent work has indicated that the SRC-3 gene is subject to amplification and overexpression in various human cancers. Some of the molecular mechanisms responsible for SRC overexpression, along with the mechanisms by which SRC-3 promotes breast and prostate cancer cell proliferation and survival, have been identified. However, the function of SRC-3 in bladder cancer remains poorly understood. In the present study, our results indicate that overexpression of SRC-3 promotes bladder cancer cell proliferation whereas knockdown of SRC-3 results in inhibition. At the molecular level, we further established that CXCR4 is a transcriptional target of SRC-3. Therefore, our study first identified that SRC-3 plays a critical role in the bladder cancer, which may be a target beneficial for its prevention and treatment.